Exosomes as a delivery tool of exercise-induced beneficial factors for the prevention and treatment of cardiovascular disease: a systematic review and meta-analysis - Lai, Zhijie; Liang, Jiling; Zhang, Jingfeng; Mao, Yuheng; Zheng, Xinguang; Shen, Xiang; Lin, Wentao; Xu, Guoqin (Frontiers in Physiology, 2023)
Exercise-derived exosomes have been identified as novel players in mediating cell-to-cell communication in the beneficial effects of improving cardiovascular disease (CVD). This review aimed to systematically investigate exosomes as delivery tools for the benefits of exercise in the prevention and treatment of CVD and summarize these outcomes with an overview of their therapeutic implications. Among the 1417 articles obtained in nine database searches (PubMed, EBSCO, Embase, Web of Science, CENTRAL, Ovid, Science Direct, Scopus, and Wiley), 12 articles were included based on eligibility criteria. The results indicate that exercise increases the release of exosomes, increasing exosomal markers (TSG101, CD63, and CD81) and exosome-carried miRNAs (miR-125b-5p, miR-122-5p, miR-342-5p, miR-126, miR-130a, miR-138-5p, and miR-455). These miRNAs mainly regulate the expression of MAPK, NF-kB, VEGF, and Caspase to protect the cardiovascular system. Moreover, the outcome indicators of myocardial apoptosis and myocardial infarction volume are significantly reduced following exercise-induced exosome release, and angiogenesis, microvessel density and left ventricular ejection fraction are significantly increased, as well as alleviating myocardial fibrosis following exercise-induced exosome release. Collectively, these results further confirm that exercise-derived exosomes have a beneficial role in potentially preventing and treating CVD and support the use of exercise-derived exosomes in clinical settings.